RANCANG BANGUN MONITORING SERVER SYSTEM BERBASIS TERMINAL LINUX DAN WHATSAPP GATEWAY STUDI KASUS: PT. XYZ - Choirrulloh Choirrulloh; Subandri Subandri (Institut Bisnis Muhammadiyah Bekasi, 2023)
This research aims to design a server monitoring system based on a Linux terminal and Whatsapp Gateway for PT. XYZ. The purpose of this system is to monitor server conditions in real-time and provide notification to the admin if there is a problem with the server. The method used in this research is by integrating the Linux terminal application with the Whatsapp Gateway using PHP programming language. The research results show that the server monitoring system based on Linux terminal and Whatsapp Gateway can provide real-time notification to the admin if there is a problem with the server, which can help in identifying and solving problems quickly. Thus, this system can improve efficiency in server monitoring and reduce downtime